2019
DOI: 10.2147/vmrr.s168227
|View full text |Cite
|
Sign up to set email alerts
|

<p>Equine viral encephalitis: prevalence, impact, and management strategies</p>

Abstract: Members of several different virus families cause equine viral encephalitis, the majority of which are arthropod-borne viruses (arboviruses) with zoonotic potential. The clinical signs caused are rarely pathognomonic; therefore, a clinical diagnosis is usually presumptive according to the geographical region. However, recent decades have seen expansion of the geographical range and emergence in new regions of numerous viral diseases. In this context, this review presents an overview of the prevalence and distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 123 publications
(107 reference statements)
0
18
0
3
Order By: Relevance
“…Finally, the titers of the IgM antibody, mediated by the virus, were highly elevated (21). Despite the success of these studies, and the fact that VEEV continues to plague certain regions (24)(25)(26), no studies known to the present authors have been performed to determine whether melatonin would be an effective treatment of VEEV in equine or human species.…”
Section: Melatonin/virus Interactionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, the titers of the IgM antibody, mediated by the virus, were highly elevated (21). Despite the success of these studies, and the fact that VEEV continues to plague certain regions (24)(25)(26), no studies known to the present authors have been performed to determine whether melatonin would be an effective treatment of VEEV in equine or human species.…”
Section: Melatonin/virus Interactionsmentioning
confidence: 87%
“…A group of South American scientists (21)(22)(23) tested the utility of melatonin as a preventative molecule against Venezuelan equine encephalitis virus (VEEV). This group had ample reason to examine this association since VEEV is a common mosquito-borne organism which is pathological to not only equine species but to humans as well (24) and it has infected thousands of humans and domestic equine species in northern South America especially (25). Using a mouse model of the disease, Bonilla and colleagues (21)(22)(23) found that melatonin, in three individual studies, delayed the development of VEEV disease, deferred the time of death, reduced the viral load in both the central nervous system and in the blood and lowered neural apoptosis and lipoperoxide concentrations as well as the mortality of the infected mice.…”
Section: Melatonin/virus Interactionsmentioning
confidence: 99%
“…However, most flaviviruses are antigenically related, which results in cross-reactivity between them, especially the SLEV, JEV, and WNV, which makes serological diagnosis more difficult [117,121]. It is often necessary to use additional confirmatory tests, especially in certain regions where there is co-circulation of those related viruses, with viral neutralization tests and plaque reduction tests (PRNT) being the most specific [119,122]. RT-PCR-based techniques can be used for direct detection of the virus and are highly specific.…”
Section: Flaviviral Encephalitismentioning
confidence: 99%
“…WNV infections, for example, have a single viremic phase of 4 to 6 days in horses. Therefore, due to the possibility of false-negative results by PCR, confirmation by serological tests is necessary, usually ELISAs for anti-viral IgM are used for this purpose [118,122].…”
Section: Flaviviral Encephalitismentioning
confidence: 99%
“…Beyond these considerations, horses share a susceptibility as accidental hosts for multiple anthropozoonotic pathogens that affect the nervous system, such as Hendra and Nipah virus (HeV, NiV), West Nile virus (WNV), Japanese encephalitis virus (JEV), Ilheus virus (ILHV), St. Louis encephalitis virus (SLEV), Powassan virus (POWV), tick borne encephalitis virus (TBEV), Western equine encephalitis virus (WEEV), Eastern equine encephalitis virus (EEEV), Venezuelan equine encephalitis virus (VEEV), Rabies virus (RV), and Borna disease virus-1 (BoDV-1) (Richt et al, 2000;Furr and Reed, 2007c;Carrera et al, 2018;Kumar et al, 2018;Barba et al, 2019;Liesche et al, 2019). Therefore, the horse serves as an indicator species for regional risk of infection and sometimes mirrors similar brain pathologies upon contagion as human patients (David and Abraham, 2016;Kumar et al, 2018;Liesche et al, 2019;Niller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%